Adverse Events in Childhood as a Risk Factor for Elevated BMI among People with Schizophrenia and Bipolar Disorder. (1st November 2016) - Guenzel, Nicholas; Houfek, Julia; Watanabe-Galloway, Shinobu
Abstract : Diseases of obesity have become a major cause of morbidity and mortality among people with schizophrenia and bipolar disorder. Childhood adversity has been associated with adult obesity in the general public, but has not been examined among people with mental illness. This study used a secondary analysis to examine childhood adversity and body mass index in people with schizophrenia and bipolar disorder. Among females, a history of physical abuse from parents or paternal emotional neglect was associated with an increased risk for obesity (OR = 3.34 and 2.44, respectively).